2016
DOI: 10.1002/ar.23458
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Fibroblasts from Different Layers of Pig Skin Exhibit Different Profibrotic and Morphological Characteristics

Abstract: In vitro studies of human dermal fibroblast (DF) heterogeneity have long been reported, yet in vivo studies and related research on animals are rare. The objectives of the study were to determine whether the DFs of pigs exhibit heterogeneity and to identify an animal model for the in vivo study of DF heterogeneity. The skin of three female red Duroc pigs (FRDPs) was separated into six layers, and the second and fifth layers (i.e., the superficial and deep dermis) were used in the establishment of wound models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Because the normal skin thickness of the FRDPs showed great discrepancy [6, 7], and the normal skin thickness was crucial for the subsequent establishment of the wound models, the thickness of the normal skin from seven anatomical locations (site A to site G) was carefully measured. It was observed that the normal skin thicknesses of the FRDPs were 2.073±0.386 mm(site A), 2.495±0.167 mm(site B), 2.313±0.311 mm(site C), 1.820±0.079 mm(site D), 2.183±0.225 mm(site E), 1.910±0.161 mm(site F), 2.383±0.264 mm(site G), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because the normal skin thickness of the FRDPs showed great discrepancy [6, 7], and the normal skin thickness was crucial for the subsequent establishment of the wound models, the thickness of the normal skin from seven anatomical locations (site A to site G) was carefully measured. It was observed that the normal skin thicknesses of the FRDPs were 2.073±0.386 mm(site A), 2.495±0.167 mm(site B), 2.313±0.311 mm(site C), 1.820±0.079 mm(site D), 2.183±0.225 mm(site E), 1.910±0.161 mm(site F), 2.383±0.264 mm(site G), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the thickness of the healed wounds was an important parameter of cutaneous fibrosis [6, 7], so the wounded skin thickness in the deep/superficial dermis group and the superficial/deep ADM group was measured. It was observed that the wounded skin thicknesses in the deep dermis group were significantly greater than those in the superficial dermis group at 2(2.510±0.138 mm, 2.173±0.219 mm, P=0.040), 4(2.334±0.147 mm, 1.997±0.184 mm, P= 0.028), and 8(2.640±0.156 mm, 2.390±0.080 mm, P= 0.029) weeks post-wounding (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations